OPTIMALISASI KEGIATAN KEUBUDIYAHAN & KESANTRIAN PERSPEKTIF KH. BAIDLOWI MUSLICH DALAM UPAYA INTERNALISASI NILAI-NILAI IBADURRAHMAN (STUDI KASUS PP. ANWARUL HUDA MALANG) - Firdaus Ainul Yaqin (UNZAH Genggong, 2022)
Malang City is one of the educational cities in Indonesia where there are various universities there. So that students in Malang City are required to have a strong mentality and condition in dealing with environmental changes that occur there. Most changes in the surrounding environment can lead to bad things so that this can affect the future of students as the next generation of the nation. Like the many acts of pornography and pornography and the existence of radical Islamic thoughts among students, this can result in the erosion of Islamic values ​​and faith in higher education circles. Pondok Pesantren, which incidentally is a place for authentic Islamic scientific treasures, can be a solution to the problems that have occurred so far. Therefore, this study reveals concrete evidence of the effect of optimizing cultural and religious activities in the context of internalizing ibadurrahman values ​​which are part of the vision and mission of the caretaker of Anwarul Huda Islamic Boarding School, namely KH. Bailowi ​​Muslich. Based on the results of the study, that there are several activities contained in the twelve characteristics of worship. The values ​​of ibadurrahman are expected to be able to influence santri (students) in strengthening Islamic values ​​and achieving life goals that are blessed by Allah SWT. Keywords: Optimization, Culturalism, Islamic religious values, Ibadurrahman values